Impact Evaluation of Fishing Boat Assistance (Case Study of Fishermen in Tomini Bay, Gorontalo Province) - Fahrudin Zain Olilingo; Ivan Rahmat Santoso (Cita Konsultindo Research Center, 2022)
The fishermen's welfare program is one of the government's concerns in the development of coastal areas. Among the forms of these efforts are the help of ships. However, along the way, it is sometimes difficult to identify the impact and success factors of the program. The purpose of this study was to analyze the impact of fishing boat assistance from the economic, socio-cultural, and institutional aspects. This study focuses on analyzing the impact and success factors of ship assistance to obtain a comprehensive picture of the sustainability of the fishing boat assistance program. The method uses the Multidimensional Scaling (MDS) technique with the help of the RAPFISH (Rapid Appraisal for Fisheries) method attributes. The results of the study found that the RSQ was 47.93% for the economic aspect, 36.37% for the cultural aspect, and 54.87% for the institutional aspect. The institutional aspect has the greatest level of sustainability. In addition, the guidance indicator is the main factor supporting and leveraging the success of fishing boat assistance. This research contributes to the description of the economic, social, and institutional impacts of fishing boat assistance so that it becomes the basis for determining government directions and policies in increasing fishing productivity in general and more specifically in the Tomini Bay Area.